Auditoria como ferramenta para a qualidade do cuidado de enfermagem em unidade de terapia intensiva de um hospital universitário - Padilha, Elaine Fátima (2010)
This evaluation study had as general purpose evaluate nursing care and record quality performed in an Intensive Care Unit of a University Hospital. It encompassed fifty patients from an Adult Intensive Care Unit through Quality Auditing. Being eighteen years of age, or older, and having a minimum of three-day stay in the ICU was among the criteria established to be part of the sampling. Data was collected from May 1st to July 31st 2009 by way of a guide proposed by Haddad which was divided in two parts: the first destined to Operational Auditing comprised of eight items and sixty-five sub items, and a second one referred to Retrospective Auditing composed of seven items and fifty-two sub items. Quality evaluation was performed in two stages. The first - Operational Auditing - consisted in observing the environment were the patient was, including execution of physical exams and in loco verification of prescribed care; the second - Retrospective Auditing - encompassed evaluation of the records taken by the nursing team. All data were recorded on Microsoft Office Excel 2007 and next, analyses was performed with the help of the Statistical Analysis System 9.1.3 software. It was considered of quality guides that obtained Positive Indexes (PI) ≥ 70% for Operational Auditing, and for Retrospective Auditing items with Complete Filling-out Percentage (FP) ≥80%; Incomplete up to 15%; no filling-out less than 15% and incorrect 0%. Among the results, care related to Physical Safety (71%) and Equipment Application (72%) were considered of quality. The remainder items did not reach quality criteria ,highlighting the ones related to Physical Activity (28%) and Oxygenation/Ventilation (29%), because they presented the lowest PIs in the study. As per records taken by the nursing team, it was confirmed that none of the items met all proposed quality criteria due to the fact that the obtained average FP was 45.6% for the Complete; 42.8% for the incomplete; 10.8% for the no filling up, and 0.8% for the incorrect. In the evaluation of nursing care for each audited month, it was observed that the ones relative to Hygiene and Comfort and to Organizational Aspects did not reach the proposed quality criteria in none of the investigated months. The remainder evaluated care showed PI ≥ 70% in at least one of the audited months. As per nursing records, it was confirmed that among all the evaluated items only the one related to Nursing Records presented an increase in FP of all answer possibilities. During auditing months, the remainder records did not show FP that approximated the determined quality criteria. We concluded that few nursing care were considered of quality and that records taken by the nursing team leave to be desired because none of the evaluated ones met all established criteria.